At the crossroads of Greco-Roman history, culture, and religion : papers in memory of Carin M.C. Green - Bell, Sinclair; Bell, Sinclair; Holland, Lora Louise; Holland, Lora Louise; Green, Carin M. C. (Archaeopress Publishing Ltd, 2018)
'At the Crossroads of Greco-Roman History, Culture, and Religion' brings together recent research from a range of upcoming and well-established scholars to demonstrate the richness of the cross-cultural exchange of ideas around the ancient Mediterranean along with the reception of and continuing dialogues with these ideas in the medieval and modern worlds. The crossroads theme both honours the memory of our late colleague and friend Carin M.C. Green, who published an important text on the cult of Diana - one of whose aspects was Trivia, the goddess of crossroads - and emphasises how each encounter of new topic or genre forces the reader to pause and think before proceeding down the new path